2017
DOI: 10.1111/papr.12637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Corticosteroids on Pain Management and Early Rehabilitation in Patients Undergoing Total Knee or Hip Arthroplasty: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Our results show that intravenous corticosteroids have good efficacy and safety when used perioperatively in total knee or hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
0
26
2
Order By: Relevance
“…According to the outcomes of this meta‐analysis, we found that corticosteroid added to a multimodal cocktail significantly reduced pain scores at rest from POD1 to POD3, decreased postoperative opioid consumption, improved knee ROM from POD1 to POD2, and decreased hospital stays. However, our results suggest that local injection of corticosteroids does not decrease inflammatory cytokines and had no effect on improving postoperative nausea and vomiting, unlike results from previous reviews of intravenous corticosteroids in arthroplasty . However, whether local corticosteroids are comparable to intravenous corticosteroids needs to be studied further.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…According to the outcomes of this meta‐analysis, we found that corticosteroid added to a multimodal cocktail significantly reduced pain scores at rest from POD1 to POD3, decreased postoperative opioid consumption, improved knee ROM from POD1 to POD2, and decreased hospital stays. However, our results suggest that local injection of corticosteroids does not decrease inflammatory cytokines and had no effect on improving postoperative nausea and vomiting, unlike results from previous reviews of intravenous corticosteroids in arthroplasty . However, whether local corticosteroids are comparable to intravenous corticosteroids needs to be studied further.…”
Section: Discussioncontrasting
confidence: 70%
“…However, our results suggest that local injection of corticosteroids does not decrease inflammatory cytokines and had no effect on improving postoperative nausea and vomiting, unlike results from previous reviews of intravenous corticosteroids in arthroplasty. 16 However, whether local corticosteroids are comparable to intravenous corticosteroids needs to be studied further. Our results revealed benefits with postoperative outcomes of TKA when a local injection of corticosteroid was added to a multimodal cocktail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-operative pain can be difficult to control and the lack of relief can lead to significant distress to patients, decreased rehabilitation participation, increased the LOS in the hospital, and increased hospital costs [15][16][17][18][19]. Opioid medications have been a mainstay of pain management strategies following orthopedic surgery; however, due to the ongoing opioid epidemic, new strategies are needed to help curb the reliance on these medications.…”
Section: Discussionmentioning
confidence: 99%